Teleste di Selinunte il ditirambografo (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2010)
Starting from a little notice in Diodorus, and proceeding with a report of  the testimonia vitae and of the fragmentary verses of the Ditirambographer Telestes of Selinus, the writer tries to reconstruct the biography and the poetics of the musician, who had his floruit between the end of the Vth and the first half of the IVth b.C.. The poet has been considered an exemplary member of the Nea Mousikè, altough the testimonies, as well as his fragmentary writings, permit to moderate this view, and to explain his position as intermediary. In particular, it is worth noting the fact that Aristoxenus, who so boldly blamed the exponents of the Nea Mousike, wrote a Life of Telestes. Neverthless, also in The De Musica of Ps- Plutarch, which owes much to the Aristoxenian perspectives and testimonies, Telestes is never listed between the Neoi Mousikoi. In the same way, in the numerous loci Athenaeus has dedicated to Telestes, it is not clearly confirmed his position as a radical innovator, and we know that in the work of Athenaeus we can find many suggestions derived from Aristoxenus and his works.